Free Ranging Desi Poultry As A Component In Maize Integrated Farming System And Its Effect On Growth And Yield Of Maize (Zea Mays L.) - M. Mohamed Amanullah, T. Ananthi, (International Journal of Scientific Research and Management (IJSRM), 2017)
A field experiment was conducted in farmers field at Devarayapuram village, Coimbatore during kharif, 2016 and winter 2016 -17 to study  the effect of introducing free ranging desi poultry in maize integrated farming system and its on growth and yield of maize. The popular maize hybrid CP 804 was used as test variety. Two farming systems viz., Maize (Aug to Nov) – Maize (Dec to  Mar) and Maize (Aug to Nov) – Maize (Dec to Mar) + desi poultry (two hens and one rooster in 3 cents) were evaluated under field conditions. The maize + desi poultry recorded better growth parameters, yield attributes and yield than maize under sole maize. Maize – Maize cropping system along with desi poultry lowered the weed density and dry weight during critical stage of the crop growth.  The increase in yield under maize + desi poultry was negligible when compared to grain yield of sole maize. The yield attributes viz., cob length, cob girth, number of grain rows cob-1, number of grains row-1, cob weight and test weight were slightly higher under maize + desi poultry farming systems. The treatment combination of maize with desi poultry recorded higher available soil nutrients (NPK) than sole maize cropping system.